2010
DOI: 10.6090/jarq.44.217
|View full text |Cite
|
Sign up to set email alerts
|

Salicylic Acid Signaling Pathway in Rice and the Potential Applications of Its Regulators

Abstract: The salicylic acid (SA) signaling pathway plays a crucial role in systemic acquired resistance in dicots. Several chemical inducers, which are also called "plant activators," such as benzothiadiazole (BTH), protect plants from diseases by acting on the SA signaling pathway. Several studies by us and other groups have revealed that rice also has the SA signaling pathway that shares signaling components with the SA signaling pathway in dicots. OsNPR1 is a rice counterpart of NPR1, a transcriptional coactivator t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 34 publications
0
17
0
Order By: Relevance
“…As an important resistance pathway against biotrophs, salicylic acid (SA), which is required for mounting the HR against an invading pathogen, induces the expression of PR genes and systemic acquired resistance (Hayat et al ., ; Takatsuji et al ., ). In TaADF7 knock‐down plants, the growth of Pst hypha increased and sporadic urediniospores occurred compared with that in control plants when inoculated with avirulent Pst .…”
Section: Discussionmentioning
confidence: 97%
“…As an important resistance pathway against biotrophs, salicylic acid (SA), which is required for mounting the HR against an invading pathogen, induces the expression of PR genes and systemic acquired resistance (Hayat et al ., ; Takatsuji et al ., ). In TaADF7 knock‐down plants, the growth of Pst hypha increased and sporadic urediniospores occurred compared with that in control plants when inoculated with avirulent Pst .…”
Section: Discussionmentioning
confidence: 97%
“…Different studies have shown that acibenzolar‐ S ‐methyl may be considered as a functional analogue of salicylic acid in the pathway leading to SAR and might act at the same binding site. Finally, acibenzolar‐ S ‐methyl‐induced resistance in rice could depend on two complementary pathways – non‐expresser of pathogenesis‐related genes (NPR1) and the transcription factor Oryza sativa WRKY45 (OsWRKY45) – with the latter being crucial for blast resistance, induced not only by acibenzolar‐ S ‐methyl but also by other products …”
Section: Profungicides For Disease Controlmentioning
confidence: 99%
“…Finally, acibenzolar-S-methyl-induced resistance in rice could depend on two complementary pathways -non-expresser of pathogenesis-related genes (NPR1) and the transcription factor Oryza sativa WRKY45 (OsWRKY45) -with the latter being crucial for blast resistance, induced not only by acibenzolar-S-methyl but also by other products. 83…”
Section: Host Plant Defence Inductionmentioning
confidence: 99%
“…However, Pb1 encodes an R protein-like CC-NB-LRR protein with atypical NB domain . Our recent studies showed that Pb1 specifically interacts with rice WRKY45 (Shimono et al 2007(Shimono et al , 2012Takatsuji et al 2010;Nakayama et al 2013;Akagi et al 2014;Takatsuji 2014), a TF that plays a major role in the salicylic acid signaling pathway, and that the blast resistance due to Pb1 is dependent on WRKY45 . Rice WRKY45 is regulated by ubiquitin-proteasome degradation in the nuclei to suppress untimely defense activation in the absence of pathogen infection .…”
Section: Introductionmentioning
confidence: 99%